A nonsurgical and nonpharmacological care bundle for preventing upper urinary tract damage in patients with spinal cord injury and neurogenic bladder. Issue 2 (21st July 2019) - Fang, Hengying; Lin, Jinxiang; Liang, Limin; Long, Xiaofang; Zhu, Xiaojia; Cai, Wenzhi
Abstract: Aim: To establish a care bundle in spinal cord injury patients with neurogenic bladder to avoid upper urinary tract damage and to provide guidance for health care staff in use of nonsurgical and nonpharmacological adjunctive strategies to improve patients' clinical outcomes. Background: Prevention of upper urinary tract damage is critical in the management of spinal cord injury patients with a neurogenic bladder, but there are no authoritative guidelines or high‐quality randomized controlled trials. Design: The study was conducted on the basis of Fulbrook and Mooney's seven‐step method for care bundle development. Data Sources: The databases PubMed, Embase, Science Citation Index, the Cumulative Index to Nursing and Allied Health Literature, the National Guideline Clearinghouse, the Cochrane Library, China Biology Medicine, China National Knowledge Infrastructure, and China Dissertation Database were searched from the date of each database's inception to April 2017. Review methods: We evaluated the literature according to the Joanna Briggs Institute evidence pre‐ranking and grade recommendation system (2014 version). The results were examined using a self‐designed data extraction. Results: A three‐element cluster including clean intermittent catheterization, bladder function training, and transcutaneous low‐frequency pulsed electrical stimulation was formed. Conclusion: The development of this bundle can provide a scientific basis for effective prevention of neurogenic upper urinary tract damage in clinical practice. SUMMARY STATEMENT: What is already known about this topic? Upper urinary tract damage is a serious complication of patients with spinal cord injury and neurogenic bladder; prevention of upper urinary tract damage is important to improve the prognosis of these patients. In the absence of authoritative guidelines, it is difficult to find a scientific basis for effective prevention of upper urinary tract damage in clinical practice. The concept of care bundles has been used to develop clinical interventions in recent years, but researchers have yet to reach a consensus on how to develop care bundles. What this paper adds? A preventive care bundle to prevent upper urinary tract damage in patients with spinal cord injury and neurogenic bladder patients was developed using the seven‐step process proposed by Fulbrook and Mooney. The prevention bundle has three elements that may reduce intravesical pressure, prevent urinary tract infection, and improve urinary‐related neuromuscular function: clean intermittent catheterization, bladder function training, and transcutaneous low‐frequency pulsed electrical stimulation. The implications of this paper: This bundle can be used in clinical practice to prevent upper urinary tract damage in patients with spinal cord injury and neurogenic bladder at high risk of upper urinary tract damage. Fulbrook and Mooney's seven‐step method is effective and can be used to develop other care bundles in different countries and topic areas.